(Un)stable architecture as deconstructed meaning - Lombard, Lindi (Rhodes University, Faculty of Humanities, Department of Fine Art, 2015)
How often do we notice the buildings that we work in, play in and live in? The architecture that we construct is specially geared to our human proportions, and shelters and accommodates us. It can be seen as a metaphor for the body, the self, and systems of social control that we have created. When the structure of this architecture is compromised, either literally or metaphorically, we experience instability and vertigo. My practical submission, Vertigo is concerned with architecture, perspective, deconstruction, instability, vertigo, scale and the body. Vertigo consists of paintings, ranging in scale from the size of a brick to the height of a single storey house. Utilizing a highly representational style as well as working with abstract sign systems and technical plan drawings, I destabilize firstly, our sense of certainty in the architecture that surrounds us, and secondly, prompts us to question the assumed fixity of ourselves and our social systems, through the convergence and collision of architecture and painting. This supporting document, (Un)stable Architecture as Deconstructed Meaning, considers the key conceptual concerns informing my practical submission. In chapter one of this mini-thesis: Deconstructivist Architecture, Instability and Impermanence I look at Deconstructivist Architecture which challenges traditional values of order, stability, harmony and unity of architecture. I position my work in relation to architecture projects on the Deconstructivist Architecture show in relation to their intent of undoing, shifting and destabilizing structure and what architecture is traditionally valued for. I also look at the shifting meaning and symbolism of architecture and skyscrapers. In the second chapter: Vertiginous Point of View and Shifted Perspectives I engage with vertigo, perspective, scale and the bodily analogy in architecture. I look at how Julie Mehretu destabilises built space and architecture in a painterly way, depicting multiple perspectives which are subjected to multiple interpretations. In chapter Three: Painting a Building and Building a Painting: Process, Scale and the Body, I discuss and engage with my practical submission, Vertigo, in relation to my process, scale, the body, vertigo, deconstruction, instability and perspective.
Keywords: Art and architecture; Architecture in art; Proportion (Art); Vertigo in art; Deconstructivism (Architecture)